Open Source Human Evolution - Andrew W. Torrance (Washington University Journal of Law & Policy, 2009)
Part I of this Article introduces the biology of evolutionary change. Part II discusses the current state of genetic engineering and its potential application to human genetic enhancement. Parts III and IV discuss the legal contours of proprietary patent and open source genetics models of innovation, respectively, and consider what differences the two alternative models might have on rates of genetic innovation and access to genetic innovations. Part V analyzes the effects that proprietary patent models and open source genetics models could have on the future trajectory of human genetic enhancement, and suggests that open source genetics would likely yield a relatively lower rate of genetic innovation coupled with democratized wider access to the resulting smaller number of genetic enhancements.
Keywords: Gene patents; Evolution; Genetic research; Human genetic engineering; Human population genetics